A geolocated dataset of German news articles - Kriesch, Lukas; Losacker, Sebastian; Justus Liebig University Giessen (My University, 2025)
The emergence of large language models and the exponential growth of digitized text data have revolutionized research methodologies across a broad range of social sciences. News data is crucial for the social sciences as it provides real-time insights into public discourse and societal trends. In this paper, we provide insights into how news articles can be geolocated and how the texts can then be further analyzed. We collect data from the CommonCrawl News dataset and clean the text data. We then use a named-entity recognition model for geocoding. Finally, we transform the news articles into text embeddings using SBERT, enabling semantic searches within the news data corpus. In the paper, we apply this process to all German news articles and make the German location data, as well as the embeddings, available for download. We compile a dataset containing text embeddings for about 50 million German news articles, of which about 70% include geographic locations. The process can be replicated for news data from other countries.
Keywords: ddc:910